A Comprehensive Systematic Review of The Role of Vasopressors in Early Management of Hemorrhagic Shock - Mohamad Fadli; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2026)
Introduction: The role of vasopressors in the early management of hemorrhagic shock remains controversial, with conflicting evidence from observational studies and randomized controlled trials. This systematic review aims to evaluate the efficacy and safety of early vasopressor administration in adult patients with hemorrhagic shock. Methods: A systematic review was conducted screening studies based on predefined criteria: adult patients with hemorrhagic shock from any cause, evaluation of any vasopressor agent within the first 24 hours, comparative study designs reporting clinically relevant outcomes. Fifty-eight sources were identified including randomized controlled trials, observational studies, and systematic reviews. Data were extracted on patient populations, vasopressor interventions, mortality outcomes, hemodynamic effects, fluid requirements, and adverse events. Results: Randomized controlled trials demonstrated that low-dose norepinephrine (<0.3 µg/kg/min) concurrent with fluid resuscitation significantly reduced 24-hour mortality (3% vs 13%, p<0.05) and in-hospital mortality (9% vs 21%, p<0.05) (Mohamed et al., 2024). The AVERT-Shock trial found no mortality difference with low-dose vasopressin but showed reduced blood product requirements (1.4 L vs 2.9 L, p=0.01) (Sims et al., 2019). Observational studies consistently associated vasopressor use with increased mortality (Aoki et al., 2018; Plurad et al., 2011; Fisher et al., 2020), though propensity-score analyses attenuated this association (Gauss et al., 2018). Vasopressors consistently achieved hemodynamic stabilization with improved mean arterial pressure and reduced fluid requirements. Adverse event profiles were similar between groups, with vasopressin associated with fewer deep venous thromboses (Sims et al., 2019). Discussion: The apparent contradiction between observational and randomized evidence is explained by confounding by indication, where sicker patients preferentially receive vasopressors. Context-dependent effects, agent-specific considerations, and timing of administration significantly influence outcomes. Low-dose vasopressors appear safe when used as adjuncts to—not replacements for—hemorrhage control and volume resuscitation. Conclusion: Early low-dose vasopressor administration, particularly norepinephrine and vasopressin, may be beneficial in selected patients with hemorrhagic shock, improving hemodynamic stability and reducing transfusion requirements without increasing mortality. Further research is needed to optimize agent selection, dosing strategies, and timing of initiation.